Modifications in the population of spontaneous plants in the presence of green manure - Favero, Claudenir; Jucksch, Ivo; Alvarenga, Ramon Costa; Costa, Liovando Marciano da (Pesquisa Agropecuaria Brasileira, 2001)
Green manure can cause modifications in the population of spontaneous plants (weeds) due to allelopatic effects and competition for light, water, oxygen and nutrients, with the possibility of eliminating some of them. On the other hand, legume crops may favor species with higher capacity of nutrients cycling and biomass production, due to improvements that they promote in the soil conditions. The objective of this work was to evaluate the alteration in the number of spontaneous crops by legume crops used as green manure. The experiment was carried out in Sete Lagoas, MG, Brazil, at Embrapa-Centro Nacional de Pesquisa de Milho e Sorgo in a typical dystrophic Latosol under Aw (seasonal tropical Savannah) climate. The experiment consisted of six treatments, five of which were legume crops jack bean, "feijão-bravo", mucuna, lab-lab and pigeonpea grown together with spontaneous plants, and one was the witness treatment (only plowed soil and fallow), with the legumes being cropped for two years. "Feijão-bravo", mucuna and jack bean were the legumes with highest biomass yield. Mucuna is the species of cover plant with the highest potential for soil coverage and suppression of spontaneous crops. The use of legumes as green manure promotes modifications in the sequential dynamics of spontaneous species.